The impact of online food delivery services on the financial performance of restaurant businesses in Malaysia - Ibrahim, Muhammad Azman; Ruslan, Rafiatul Adlin Hj Mohd; Abd Hamid, Nor Harlina; Bin Abdullah, Mohamad Fariz (Journal of Entrepreneurship, Business and Economics, 2022)
The food delivery industry is evolving and accelerated significantly in 2020 as a result of the COVID-19 pandemic, which made dine-ins impossible. The appeal of consumers to the approach of online food ordering is growing significantly, which has changed the way many consumers and food businesses interact. Many consumers and food business operators rely on food delivery platforms during movement control orders (MCO) with the no dine-in ruling. However, some businesses reported operating at a loss due to the platform's exorbitant delivery charges and hidden fees. As a result, the impact on food delivery services is hotly debated, and it is unclear whether online food delivery services improve business financial performance. Measuring financial performance, rather than just marketing triumphs, can determine how well a business is doing. Furthermore, studies on the impact of food delivery services on businesses are critical because this market is expected to grow significantly in the coming years. By using delivery services helps food businesses expand their operation outside their location as the delivery coverage. A propensity score matching analysis is proposed in this conceptual study to estimate causal treatment effects. The propensity score matching method is used to correct sample selection bias caused by structured questionnaires distributed to Malaysian restaurant businesses to collect primary data on observable differences between treatment and control groups. This conceptual research aims to assess the impact of food delivery services on restaurant financial performance in Malaysia. The relationship between food delivery services is expected to drive business financial performance.e Research paper Keywords: Food delivery, online platform, restaurant, Malaysia, financial performance, propensity score matching Reference to this paper should be made as follows: Ibrahim, M. A., Ruslan, R. A. H. M., Abd Hamid, N. H., & Bin Abdullah, M. F. (2022). The impact of online food delivery services on the financial performance of restaurant businesses in Malaysia. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 55–70.